The ideal -Hausdorff, -regular and -normal spaces. (2020)
We introduce and study new extensions of some separation axioms to ideal topological spaces, which we have called -Hausdorff, -regular and -normal. These extensions are quite natural and represent a good improvement over other extensions that have been produced recently, where there is no perceived level of separation that can be considered acceptable.